Aplikasi Bahan Organik pada Piringan Kelapa Sawit untuk Meningkatkan Populasi Cacing Tanah dan Ketersediaan Hara P dan K - Nur Ulina Warnisyah S Sebayang; T. Sabrina; Mariani Sembiring (Jurnal Agroekoteknologi, 2016)
The earthworm contribute to soil fertility and environment quality but they need a suitable habitat to survive on the land including the presence of organic material as a food source. The present study was conducted in Sei Pancur Plantation, Tanjung Morawa, in March - September 2015. The design used in study was a factorial randomized block design consists two factors. The first was various types of organic materials : without organic matter (B0) ; litter (B1) ; empty fruit bunches oil palm (B2) ; litter+T.harzianum (B3) ; and empty fruit bunches oil palm+T.harzianum (B4). The second were method of application : evenly spread a layer (C1) ; stacked around turn rod (C2) ; and stacked on the edge of weeded circle (C3). The result found that application of organic materials significantly increased P-available, K-exchangeable, and earthworm. Method of applications significantly increased P-available and earthworm populations. The relationship among interaction of both significantly increased phosphate available and earthworm populations. Application on the edge of weeded circle was the best way to reduce P-available and earthworm populations. Empty fruit bunches oil palm+T.harzianum reduced K-exchangeable. Empty fruit bunches oil palm increased earthworm populations and litter+T.harzianum increased P-available.Key words : earthworm, method of applicaton, weeded circle, organic materialsThe earthworm contribute to soil fertility and environment quality but they need a suitable habitat to survive on the land including the presence of organic material as a food source. The present study was conducted in Sei Pancur Plantation, Tanjung Morawa, in March - September 2015. The design used in study was a factorial randomized block design consists two factors. The first was various types of organic materials : without organic matter (B0) ; litter (B1) ; empty fruit bunches oil palm (B2) ; litter+T.harzianum (B3) ; and empty fruit bunches oil palm+T.harzianum (B4). The second were method of application : evenly spread a layer (C1) ; stacked around turn rod (C2) ; and stacked on the edge of weeded circle (C3). The result found that application of organic materials significantly increased P-available, K-exchangeable, and earthworm. Method of applications significantly increased P-available and earthworm populations. The relationship among interaction of both significantly increased phosphate available and earthworm populations. Application on the edge of weeded circle was the best way to reduce P-available and earthworm populations. Empty fruit bunches oil palm+T.harzianum reduced K-exchangeable. Empty fruit bunches oil palm increased earthworm populations and litter+T.harzianum increased P-available.Key words : earthworm, method of applicaton, weeded circle, organic materials